Demokrasi dan Transparansi Partai Kebangkitan Bangsa Dalam Rekrutmen Caleg Pada Pemilu 2019 - Ruslan, Muhammad; Separera Niron, Eusabius (Jurnal Inovasi Ilmu Sosial dan Politik (JISoP), 2020)
This article aims to take photos and browse in critical problems of democracy and transparency of the Kebangkitan Bangsa Party in the recruitment of candidates in the 2019 elections. The recruitment process in political parties includes three stages, namely certification, nomination, and election. Through qualitative research with analytical-critical description method, this paper argues that the mechanism of political recruitment in the Kebangkitan Bangsa Party through an undemocratic and untransparent process, where prospective legislative candidates who register to become prospective legislative candidates only submit registration forms and various completeness of the other files and henceforth the prospective candidates are only waiting for the process of determining the serial number of candidate by the leadership of political parties. In addition, the position number is determined without going through the readiness and competency test mechanism of the candidates.